Biopolitics and literature: the disiecta membra of the present time in Feliz ano velho - Vecchi, Roberto (Revista do Instituto de Estudos Brasileiros, 2007)
Combining a critical approach on cultural representation and some biopolitical concepts, the essay aims to discuss how representation constraints - referred particularly to an authoritarian context - may find a possibility to express extreme or unutterable experiences, such as violence or death together with the victim's body elimination, which excludes the possibility of mourning. This case study analyses the novel Feliz ano velho (1982), by Marcelo Rubens Paiva, which pseudo-simple narrative enables us to deepen the most radical questions on cultural criticism through an interdisciplinary perspective.